Contesting 'Permit-and-Licence Raj': Economic Conservatism and the Idea of Democracy in 1950s India. Issue 1 (3rd November 2020) - Balasubramanian, Aditya
Abstract: Economic conservatism in India traces its roots in the fragmentation of political consensus following the success of the anti-colonial nationalist movement. Framed in the context of the Cold War, long before the 1991 liberalization reforms, this economic conservatism blended anti-communism, free-market advocacy, and the defence of property. This was expressed as the central agenda of the broadly secular Swatantra Party, an effort to consolidate two-party democracy that emerged by the late 1960s as the most serious challenger to the dominant Congress Party. Swatantra brought together diverse progenitors aligned with American development ideas for the Third World. This article reconstructs Indian economic conservatism's transnational history through an interconnected study of three founding figures of the party and the network of urban associations and periodicals brewing alternative ideas beneath the layers of dominant opinion in which they were embedded. It recasts non-aligned India as a site of ideological contestation affected by the Cold War. Swatantra's lasting critique of Indian political economy was indicative of a more widely held dissent on India's development strategy, which has helped to drive the fragmentation of Indian politics. Demands for the party's revival reveal a desire for a secular alternative to the ruling Bharatiya Janata Party.